2017
DOI: 10.1002/jnr.24083
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia/lymphoma‐related factor (LRF) exhibits stage‐ and context‐dependent transcriptional controls in the oligodendrocyte lineage and modulates remyelination

Abstract: Leukemia/lymphoma-related factor (LRF), a zinc-finger transcription factor encoded by Zbtb7a, is a protooncogene that regulates differentiation in diverse cell lineages, and in the CNS, its function is relatively unexplored. This study is the first to examine the role of LRF in CNS pathology. We first examined LRF expression in a murine viral model of spinal cord demyelination with clinically relevant lesion characteristics. LRF was rarely expressed in oligodendrocyte progenitors (OP) yet, was detected in nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Milled CPZ powder (cat #14690; Sigma-Aldrich; St. Louis, MO) was mixed as 0.3% CPZ in normal chow (diet TD.01453; Harlan Teklad, Frederick, MD) to form pellets that were refreshed every 2-3 days. A dose of 0.3% CPZ in pellets produces CC demyelination approximately equivalent to 0.2% CPZ powder in ground chow [37][38][39]. Cohorts to be evaluated for remyelination received normal chow pellets for an additional 2 weeks after CPZ removal.…”
Section: Mice and Cuprizone Model Of Demyelinationmentioning
confidence: 99%
“…Milled CPZ powder (cat #14690; Sigma-Aldrich; St. Louis, MO) was mixed as 0.3% CPZ in normal chow (diet TD.01453; Harlan Teklad, Frederick, MD) to form pellets that were refreshed every 2-3 days. A dose of 0.3% CPZ in pellets produces CC demyelination approximately equivalent to 0.2% CPZ powder in ground chow [37][38][39]. Cohorts to be evaluated for remyelination received normal chow pellets for an additional 2 weeks after CPZ removal.…”
Section: Mice and Cuprizone Model Of Demyelinationmentioning
confidence: 99%
“…4C, Table S4). Although cell-free hemoglobin could indeed induce microglial in ammatory response for neuronal injury 32,33 , transcripts of hemoglobin are thought to come from hematopoietic stem cells rather than peripheral blood cells. It is suggested that a proportion of microglia might synthesize hemoglobin, and the consequent toxic effect of endogenous breakdown product hemin may be a novel source of hemoglobin in intracerebral hemorrhage and neuronal injury.…”
Section: Discussionmentioning
confidence: 99%